2012
DOI: 10.1016/j.expneurol.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal transplantation of GABAergic neural progenitors attenuates neuropathic pain in rats: A pharmacologic and neurophysiological evaluation

Abstract: Dysfunctional γ-aminobutyric acid (GABA)-ergic inhibitory neurotransmission is hypothesized to underlie chronic neuropathic pain. Intraspinal transplantation of GABAergic neural progenitor cells (NPCs) may reduce neuropathic pain by restoring dorsal horn inhibition. Rat NPCs pre-differentiated to a GABAergic phenotype were transplanted into the dorsal horn of rats with unilateral chronic constriction injury (CCI) of the sciatic nerve. GABA signaling in antinociceptive effects of NPC grafts was tested with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 61 publications
6
50
0
Order By: Relevance
“…In the spinal cord, local interneurons and descending inhibitory circuits modulate pain sensations that are processed in the superficial layers of the dorsal horn. The neurotransmitter GABA released by these interneurons plays a major role in pain modulation, as pharmacological blockade of GABA-ergic neurotransmission or deletion of specific subunits of GABA receptors in the spinal cord leads to hyperalgesia (exacerbated pain) and allodynia (Gwak et al, 2006;Jergova et al, 2012). Allodynia is a state of increased response of neurons to repetitive painful stimulation, and pain response to stimulus from skin that typically does not elicit pain (e.g.…”
Section: Gaba-ergic Cell Therapy For Relieving Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…In the spinal cord, local interneurons and descending inhibitory circuits modulate pain sensations that are processed in the superficial layers of the dorsal horn. The neurotransmitter GABA released by these interneurons plays a major role in pain modulation, as pharmacological blockade of GABA-ergic neurotransmission or deletion of specific subunits of GABA receptors in the spinal cord leads to hyperalgesia (exacerbated pain) and allodynia (Gwak et al, 2006;Jergova et al, 2012). Allodynia is a state of increased response of neurons to repetitive painful stimulation, and pain response to stimulus from skin that typically does not elicit pain (e.g.…”
Section: Gaba-ergic Cell Therapy For Relieving Neuropathic Painmentioning
confidence: 99%
“…LGE cells into the ipsilateral lumbar gray matter of the spinal cord a week after nerve constriction (Jergova et al, 2012, Table 2). Grafting into the dorsal horn of the spinal cord decreased hypersensitivity, heat hyperalgesia, cold allodynia and exaggerated neuronal firing at 1-3 weeks post-grafting.…”
Section: Gaba-ergic Cell Therapy For Relieving Neuropathic Painmentioning
confidence: 99%
“…Not surprisingly, therefore, the most common therapies for neuropathic pain rely on anti-convulsants with proven efficacy in the management of epilepsy, another condition associated with hyperexcitability. An alternative is to take a disease-modifying therapeutic approach, namely one that restores inhibitory tone by rewiring inhibitory circuits in the spinal cord [22]. Following upon the studies of Baraban et al [2] in a mouse model of epilepsy, w demonstrated that intraspinal transplantation of precursors of cortical GABAergic interneurons derived from the mouse medial ganglionic eminence (MGE) can completely reverse the mechanical hypersensitivity produced in a peripheral nerve injury model of neuropathic pain [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, knockout of inhibitory neurons or blockade of these neurons receptors induce allodynia and hyperalgesia (32,36). But ablating of apoptotic GABAergic interneurons or transplantation of GABAergic neural progenitors attenuates neuropathic pain in rats (32,37,38). These data suggested that inhibitory interneurons play a key role in neuropathic pain processing.…”
Section: Disinhibition Of Spinal Gabaergic Interneurons and Neuro-patmentioning
confidence: 98%
“…Several possible mechanisms have been proposed for the disinhibition of inhibitory interneurons in spinal dorsal cord after nerve injury. These mechanisms include loss of spinal interneurons, reduction of transmitter release, diminished activity of these cells and decreased effectiveness of inhibitory interneurons (38).…”
Section: Disinhibition Of Spinal Gabaergic Interneurons and Neuro-patmentioning
confidence: 99%